Identifikasi Kesalahan Dalam Menyelesaikan Soal Volume Bangun Ruang Pada Siswa Kelas Vi Sdn Durensawit 02 Kecamatan Kayen Kabupaten Pati Tahun 2016 - Rudiyanto, Rudiyanto; , Dr.Sumardi,M.Si (2017)
Mathematics courses given to students ranging from elementary school to equip the ability of logical thinking, analytical, systematic, critical, and creative, as well as the ability to cooperate. Mathematics subjects considered difficult by students, so students often make mistakes in solving math problems one of which is about the volume of geometry. In accordance with these problems the objectives to be achieved in this research is to describe the type of factor, as well as solutions to problems. In this study, researchers sought to describe the problem is and how pemecahkan problem, then it is relevant if this study was conducted using qualitative approach with descriptive methods. Based on the research results as well as referring to the purpose of the study it can be concluded that these types of errors do students include misconceptions, false beliefs, operation errors, and errors of fact. Factors causing the errors students come from teachers and students. Teachers use teaching methods with a lot of lecturing and minimal use of props, it makes the children are not able to absorb the concept of volume geometry. Of students include low learning interest, not meticulous in work, not mastered the concepts, as well as the lack of the role of parents. Solutions do to overcome these problems include giving extra hours, developing teaching methods, and provide varied exercises. Keywords : identification, type of error, the error factor